Right Ventricular Clot in Transit in a Patient with Coronavirus Disease 2019 (COVID-19) Pneumonia Successfully Treated with Thrombolytics - Yaman Alali; Ian Jackson; Abedel Rahman Anani; Marisa Varghese; Muhammad Ebrahim Khan; Suchitra Pilli (Case Reports in Critical Care)
Background. Right heart thrombus or clot in transit is a rare venous thromboembolism (VTE) with high mortality. COVID-19 infection has been associated with increased risk of such events. We present the case of a 63-year-old man with no traditional VTE risk factors who was diagnosed with a clot in transit three weeks after diagnosis of COVID-19. Clinical Case. A 63-year-old male with no significant past medical history who presented to the emergency department with shortness of breath. He tested positive for COVID-19 three weeks prior. His oxygen saturation was 60% on room air and was put on nonrebreather mask. He was still showing signs of respiratory distress including tachypnea, tachycardia, diaphoresis, and accessory muscle use. The patient was subsequently intubated and mechanically ventilated. Chest computed tomography with contrast showed acute bilateral pulmonary emboli with flattening of the interventricular septum suggestive of right heart strain. Bedside echocardiogram showed severely enlarged right ventricle with reduced systolic function and evidence of right ventricular strain and a mobile echodensity in the right ventricle attached to the tricuspid valve consistent with a clot in transit. The patient was treated with full dose systemic thrombolysis with rapid improvement in his symptoms. He was extubated the following day and a repeat echocardiogram showed resolution of the clot in transit. Conclusion. Clot in transit is rare but can occur in COVID-19 patients even in the absence of traditional thromboembolism risk factors. Management includes systemic anticoagulation, systemic thrombolysis, and surgical embolectomy. Our patient was successfully treated with systemic thrombolysis.